Whose job is it anyway? Organisational IS/IT competencies for value creation - Peppard, Joe (Cranfield University, 1998)
Research highlights that business managers are continually disappointed with the value which they perceive they are deriving from their IT investments. The dominant perspective of the IS literature and business practice is that creating value through IT is primarily the responsibility of the IT organisation. Accordingly, to address this chronic malaise attention focuses on the IT organisation with proposed prescriptions ranging from re-skill the IS professional to re-engineer the IT organisation to the ultimate sanction of outsourcing. This paper examines this problem of value creation through IT from an organisational as opposed to a functional perspective. Drawing on the Resource-Based View of the firm the paper argues that the effective deployment and exploitation of IT should be viewed as a “strategic asset”. As such, organisations must develop IS/IT competencies and that these competencies are distributed across the organisation and not solely in the IT organisation. Through a multi-methodological approach these organisational IS/IT competencies are identified, defined and validated. The resultant competencies are then evaluated in the context of a single organisation. The paper ends with some conclusions and further research directions and opportunities.